A novel gamification-based approach for encouraging personal hand hygiene - Rice, Charles Edward Frederico (2014)
Washing of one's hands is not only to remove visible dirt but the invisible bacteria, pathogens and more that can cause illness and in rare cases, death. When considering the multitude of industries that rely on clean hands such as healthcare, food manufacture and preparation, services such as waitressing the negative implications become apparent; not to mention the personal hand hygiene for everybody's day-to-day lives. This dissertation paper sought to investigate this application area by evaluating the literature and understanding the problem so that a technological solution can be created. Domains of knowledge such as Ergonomics, Human-Computer Interaction, Psychology, Game Design and the emerging Gamification field lend knowledge to assist developing a motivational hand wash platform. An ethnographic study at manufacturing places of work and hierarchical task analysis were carried out to identify problem areas where people could improve, found to be lack soap usage and short wash length. After experimentation with different solutions a Smartwatch was chosen and SmartWash was developed using a variety of interaction design techniques with the aim to increase the occurrence and length of a person's hand washing habits. A lab and field experiment were carried out on recruited participants for several days to ascertain if SmartWash made a difference to a person's performance or attitude and additionally measuring usability for this style of solution. Results indicated that no significant differences in performance or attitude was measured, however the usability was rated as high. This could be due to the briefness of the study length, small sample size or the application itself thus requiring further study. Contributions have been made for testing interaction design of a "Smart" wrist watch and are a step in the right direction for creating a widely usable and available means of improving practical hand washing.